ClariVein® – Early results from a large single-centre series of mechanochemical endovenous ablation for varicose veins. (February 2017) - Tang, TY; Kam, JW; Gaunt, ME
Objectives: This study assessed the effectiveness and patient experience of the ClariVein® endovenous occlusion catheter for varicose veins from a large single-centre series in the UK. Methods: A total of 300 patients (371 legs) underwent ClariVein® treatment for their varicose veins; 184 for great saphenous vein (GSV) incompetence, 62 bilateral GSV, 23 short saphenous vein (SSV), 6 bilateral SSV and 25 combined unilateral great saphenous vein and SSV. Patients were reviewed at an interval of two months post procedure and underwent Duplex ultrasound assessment. Postoperative complications were recorded along with patient satisfaction. Results: All 393 procedures were completed successfully under local anaesthetic. Complete occlusion of the treated vein was initially achieved in all the patients, but at eight weeks' follow-up, there was only partial obliteration in 13/393 (3.3%) veins. These were all successfully treated with ultrasound-guided foam sclerotherapy. Procedures were well tolerated with a mean pain score of 0.8 (0–10). No significant complications were reported. Conclusions: ClariVein® can be used to ablate long and short saphenous varicose veins on a walk-in–walk-out basis. Bilateral procedures can be successfully performed, and these are well tolerated as can multiple veins in the same leg. Early results are promising but further evaluation and longer term follow-up are required.